Altitudinal runoff assessment under variable lapse rates of temperature in the Hindu Kush, Karakorum and Himalaya ranges of Pakistan - Ashraf, Arshad (International Journal of Advanced Geosciences, 2020)
Snow and glaciers form a major source of fresh water for sustenance of millions of people in the Hindu Kush, Karakoram and Himalaya (HKH) region. The meltwater supplies are highly vulnerable to changing climate which may affect irrigated agriculture, livelihoods and natural ecosystems in the region. In the present study, a correlation between ice-melt runoff, glacier area and mean temperature was developed and applied to assess glacier-melt runoff using lapse rates of temperature (LRT) in 10 river basins of the HKH ranges of Pakistan. The LRT of ablation period was determined about â€“0.39Â°C/100 m in the Hindu Kush, â€“0.67Â°C/100 m in the Karakoram and â€“0.59Â°C/100 m in the Himalayas. Maximum ice-melt runoff was estimated from 4500â€“5000 m in seven basins, whereas it was maximum from 5000â€“5500 m elevation range in two basins. In Jhelum basin, the runoff was found maximum from 4000â€“4500 m elevation range. Overall, about 28.3% of the glacier-melt appears to generate from 5000â€“5500 m and 27.8% from 4500â€“5000 m elevation range in all three HKH ranges. However, thorough glacio-hydrological studies are essential in context of possible changes in climate and land use for effective water resource management in this region in future.Â Â